Biliopleural fistula after penetrating thoracoabdominal injury: A case report. (May 2022) - Tesfaye, Samuel; Tiruneh, Abraham Genetu; Tesfaye, Mahlet; Gulilat, Dereje
Abstract: Introduction: Biliopleural fistula is a rare complication of thoraco-abdominal injury. Due to its rarity, the experience of any one surgeon is minimal, there is a paucity of literature regarding optimal treatment. This case report can be an addition to the existing reports to guide surgeons in better understanding and management of such cases. Case presentation: A 30 yrs old male patient presented 2 weeks after he sustained gunshot injury over the right posterior chest. He was referred to our hospital because there was bilious chest tube output. Thoracotomy was done and finding was 10 cm right diaphragmatic defect with lacerated liver oozing bile and subcapsular hematoma that herniated into chest. Clotted blood had trapped the lung with pleural peel. Clot evacuation, decortication, biliary leak and liver laceration repair was done. The diaphragmatic defect was then closed. Patient had smooth postoperative course. Discussion: Patients with BPF after thoracoabdominal injury can present with shortness of breath, bile output through chest tube and pleural effusion. Since bile has corrosive effect on lung with subsequent complications like empyema and bronchobiliary fistula, early diagnosis and treatment are imperative. BPF after thoracoabdominal injury can be effectively managed with thoracotomy, decortication and closure of diaphragmatic defect. Conclusion: Biliopleural fistula is uncommon after penetrating thoraco-abdominal injury and high index of suspicion and early diagnosis are of paramount importance to prevent complication. Surgery is best treatment option to stop biliary leak, close the diaphragmatic defect, manage further injuries in the chest and release trapped lung. Highlights: Biliopleural fistula (BPF) is a communication between biliary tree and pleural cavity. BPF can occur after iatrogenic, malignant or inflammatory conditions. BPF after thoracoabdominal injury is a rare occurrence. Bile has corrosive effect on lung with subsequent complications like empyema and bronchobiliary fistula. BPF after thoracoabdominal injury can be managed with thoracotomy, decortication and closure of diaphragmatic defect.